Virus-Negative Necrotizing Coronary Vasculitis with Aneurysm Formation in Human SARS-CoV-2 Infection - Andrea Frustaci; Marco Francone; Romina Verardo; Maria Rosaria Capobianchi; Cristina Chimenti (MDPI AG, 2021)
We report a case of myopericarditis associated to SARS-CoV-2 infection with necrotizing coronary vasculitis of intramural vessels, giving rise to biventricular apical microaneurysms and to electrical instability. Negativity of myocardial polymerase chain reaction for the most common cardiotropic viruses and for SARS-CoV-2 suggested an immune-mediated myocardial and pericardial inflammatory disease. High dose (1 mg/Kg daily) prednisone and anti-viral (Remdesivir, IDA Business, Carrigtohill, County Cork, T45 DP77, Ireland) therapy led to resolution of cardiac inflammation and ventricular arrhythmias. Morpho-molecular characterization of endomyocardial tissue may improve the outcome in subjects with SARS-CoV-2-associated myopericarditis and coronary vasculitis.